Copula-based Wetness-Dryness Encountering Analysis of Upstream Runoff in the Pearl River Delta - ZHANG Zhaoyi; HE Yanhu; LIN Zhuliang; CHEN Xiaohong (Renmin Zhujiang, 2021)
Study on the wetness-dryness encountering of the main tributaries of the Pearl River (i.e.,the West River (WR),North River (NR) and East River (ER)) under the changing environment,is conducive to the allocation and regulation of water resources in the Pearl River Delta(PRD) during the dry season to ensure the water supply security of the PRD city cluster.Based on the monthly average inflow of the WR,NR and ER,the Copula functions were used to construct the two-dimensional and three-dimensional joint distribution of the inflow of the three rivers at the annual,flood and dry period scales,and the laws of the wetness-dryness encountering of the three rivers were explored.The results show that the Frank Copula function can fit the two-dimensional and three-dimensional joint distribution of the upstream inflow better.The probability of synchronized wetness-dryness two-dimensional combinations of WR,NR and ER are higher when compared to that of the three-dimensional combination of wetness-dryness.The 3-dimensional wetness-dryness encounter combinations of “extreme dryness-extreme dryness-more dryness” and “extreme dryness-more dryness-more dryness” are more likely to happen in dry years.The upstream inflow under the 3-dimensional wetness-dryness encounter combinations of “extreme dryness-extreme dryness-more dryness” and “extreme dryness-more dryness-more dryness” are less during the dry season,which would pose greater challenge for the cities water supply in the PRD.